The Effectiveness of Organizational Culture on Quality of Work - Ai Mulyaningrum; Faizal Mulia Z; Nor Norisanti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
Organizational culture is something to pay attention to in a company because it can affect the quality of work of its employees. Quality employees can work well if a good culture is created and will infect other employees. This study aims to determine the effect of organizational culture on the quality of work of PT. Citra Van Titipan Kilat (TIKI) Sukabumi City. The method used in this research is the quantitative method, the population in this study were employees of PT. Citra Van Titipan Kilat (TIKI) Sukabumi City. A population of 57 respondents at PT. Citra Van Titipan Kilat (TIKI). The results of the f-test research on the organizational culture variable showed the calculated f value in this study was 7.234 with a significant value of 0.000, the significant value of 0.000 was smaller than 0.05 (0.000> 0.05). So it can be interpreted that the variable organizational culture has a positive effect on the quality of work for PT. Citra Van Titipan Kilat Sukabumi City.